A construção do conceito de Tempo Histórico para crianças autistas na Educação Básica - JESUS, Victória Costa de (2023)
According to the Federal Constitution of 1988, Law No. 9394/1996 of Guidelines and Bases of Education (LDB) and Law No. 8069/1990, known as the Statute of the Child and Adolescent (ECA), everyone has the right to education. In 2012, Law No. 12,796/2012 (known as the Berenice Piana Law) included in this framework of rights the assistance to citizens with Autism Spectrum Disorder (ASD) and, more specifically, children. However, despite a whole legal apparatus that guarantees the access of this public to schools, it is possible to analyze that, with regard mainly to the Institutions supported by the Municipalities within the State, the training of teachers and the various professionals of Basic Regular Education is still precarious and minimal compared to the great demand of autistic students. Therefore, this research seeks, through the problematization of the training of the History teacher of Basic Education, knowledge about the concept of School Culture, to apply the concept of Temporality from the skill EF06HI01 of the BNCC referring to the 6th year of Elementary School to autistic children of level 1 and 2 in order to promote a teaching aimed at the inclusion of the autistic public to the usual and interdisciplinary methodologies required in the teaching of History.